The role of political leadership in the development of the State of Malaysia; Mahathir Muhammad as an example - Qabaha, Mahmoud Gawdat; Abu Jaber, Ibrahim Hassan (Journal of Economic, Administrative and Legal Sciences, 2022)
this study sought to identify the role of the Malaysian political leadership in development during the rule of "Mahathir Muhammad", and the researcher adopted the descriptive analytical approach, through Describe the experience of the political leadership during the rule of "Mahathir Muhammad" in Malaysia, and analyze its results to show the extent of its success in achieving its goals. The study concluded that; That the Malaysian experience is a successful one, and that there is a positive correlation between the role of political leadership during the rule of "Mahathir Muhammad" and development in the State of Malaysia, as he was a successful model as a political leader who promoted his people and his country with comprehensive development until the Malaysian experience became a role model, and in light of this result The study made several recommendations, the most prominent of which were: the necessity of studying the models of successful political leaders who contribute to the development of their countries, studying the role of higher administrations in creating and applying values ​​and putting pressure on decision-makers for change and comprehensive and sustainable development, and dissolving any sectarian, ethnic and religious conflicts and transforming them into a union that is in the interest of a renaissance The state, and combating all forms of corruption, as it undermines comprehensive and sustainable development efforts.
Keywords: political leadership; development